Atlas of the ancient world (London : Maris Multimedia, 1997)
Features: 44 major civilizations, 52 documents, 7 magnificent VR reconstructions of ancient buildings, 11 interactive excavations, 2000 colour illustrations plus maps, 200,000 words of commentary, 17 reconstructions of ancient music
Windows 95, pentium 90 processor, 16 MB RAM, 4 speed CD-ROM drive, 640 X 480 resolution
Keywords: History, Ancient; Architecture, ancient; Civilization, Ancient